Association of ABCB1 genetic polymorphisms with susceptibility to colorectal cancer and therapeutic prognosis. (June 2013) - Wu, Huizhe; Kang, Hui; Liu, Yong; Xiao, Qinghuan; Zhang, Yining; Sun, Mingjun; Liu, Duo; Wang, Zhe; Zhao, Haishan; Yao, Weifan; Jia, Tianhong; Wang, Enhua; et al.
Aim: To evaluate the association of ABCB1 gene polymorphisms with susceptibility to colorectal cancer (CRC) and clinical outcomes of CRC patients with chemotherapy.Patients & methods: A case–control study was performed on the C3435T, C1236T and G2677T/A polymorphisms in the ABCB1 gene in 1028 CRC patients and 1230 controls.Results: We observed that the ABCB1 C3435T and G2677T/A variants as well as the 3435T–1236T–2677T haplotype significantly increased the risk of CRC. The ABCB1 C3435T CT genotype had a significant effect on the time to recurrence (adjusted hazard ratio [HR; 95% CI]: 0.560 [0.355–0.882]; p = 0.012). Moreover, ABCB1 C1236T variant carriers displayed a longer overall survival after postoperative oxaliplatin-based chemotherapy (adjusted HR [95% CI]: 0.354 [0.182–0.692], 0.646 [0.458–0.910], respectively). In addition, 1236TT–2677TT–3435TT haplotype carriers showed a worse progression-free survival (adjusted HR [95% CI]: 1.477 [1.012–3.802]; p = 0.043) and recurrence-free survival (adjusted HR [95% CI]: 2.183 [1.253–3.802]; p = 0.006).Conclusion: The ABCB1 polymorphisms might be a candidate pharmacogenomic factor to assess susceptibility and prognosis after oxaliplatin-based chemotherapy for CRC patients. Original submitted 4 January 2013; Revision submitted 10 April 2013